Analisis Kadar Pati Resisten, Total Serat dan Daya Terima Kabosol Tersubstitusi Tepung Pisang Kepok Termodifikasi - Firdaus Syafii; Yudianti Yudianti (Jurnal Kesehatan Manarang, 2022)
Kepok banana flour is a processed food that has the potential to be used as a functional food. One of the efforts to improve the functional food of banana kepok flour is Modification. Modified kepok banana flour can increase the levels of resistant starch and total fiber. Modified kepok banana flour can be used in the manufacture of processed food typical of Mandar, namely kabosol. This study aims to determine the effect of adding modified kepok banana flour to kabosol on resistant starch content, fiber content and product acceptability. This research is an experimental study with a post-test design.The research design used a completely randomized design (CRD) with five factors. They were F0 (0%), F1 (25%), F2 (50%), F3 (75%), and F4 (100%). Parameters measured were resistant starch content, total fiber, and hedonic test (taste, aroma, color, and texture). The data was processed using the ANOVA test at a 5% confidence interval. Based on the results of the study, there was an effect of adding modified kepok banana flour to kabosol based on resistant starch content (p=0.0133), fiber content (p=0.0243), and organoleptic tests (color (p=0.0208), taste (p=0.0284), aroma (p=0.0432), and texture (p=0.0459)) at a 5% confidence interval. Treatment F4 (100%) showed the highest values ​​of resistant starch and total fiber, which were 25.02 % and 20.65%. In addition, the F4 treatment (100%) gave a good acceptance of color (4.9), taste (6.1), aroma (6.0), and texture (5.1 kabosol made with the addition of 100% modified banana flour gave a significant effect on the resistance starch content, total fiber and acceptability test. Kabosol with the best treatment can be used as a preferred functional food so that it can be consumed daily, especially for weight control and people with diabetes mellitus.